Modeling potential distribution of Indo-Pacific humpback dolphins (Sousa chinensis) in the Beibu Gulf, China - Chen,Mei; Song,Yuqin; Qin,Dagong (PeerJ Preprints, 2016)
Mapping key habitats of marine mega-vertebrates with high mobility is crucial for establishing Marine Protected Area (MPA) networks. Due to difficulties in achieving sound data in the field, Species Distribution Modeling (SDM) provide an efficient alternative. As a keystone and flagship species in inshore waters in southern China, Indo-Pacific humpback dolphins (Sousa chinensis) play an important role in coastal ecosystems. We used a maximum entropy (Maxent) modeling approach to predict potential habitats for the dolphins in the Beibu Gulf of China. Models was based on eight independent oceanographic parameters derived from Google Earth Digital Elevation Model (DEM) and Landsat images, and presence-only data from boat-based surveys between 2003 and 2013. Three variables, distance from major estuaries, from coast and from 10-m isobaths, were the strongest predictors, consistent with previous studies. Apart from known areas, a new area, Beilunhe Estuary (BE) close to the boundary of China and Vietnam was predicted. Based on our findings, we proposed a regional MPA network for humpback dolphins in the Beibu Gulf of China.
Keywords: Species Distribution Modeling (SDM); Maxent; the Beibu Gulf; Indo-Pacific humpback dolphins (Sousa chinensis); Google Earth Digital Elevation Model (Google Earth DEM)